Assessment of immune responses and intestinal flora in BALB/c mice model of wheat food allergy via different sensitization methods - Chenglong Liu; Chen Chen; Xingyu Yan; Shimin Gu; Xin Jia; Wenhui Fu; Xiao Meng; Wentong Xue (Food Science and Human Wellness)
Increasing incidences showed that food allergies have attracted more and more attention from researchers. BALB/c mice were sensitized with wheat gluten combined with aluminum hydroxide adjuvant via intraperitoneal injection, transdermal sensitization, and oral gavage sensitization route. Results showed that all the three sensitization methods could induce allergic symptoms; increase the serum antibody (total immunoglobulin E (IgE), specific IgE, IgG, IgA) and histamine content; promote the secretion of Th2 cytokines (interleukin (IL)-4, IL-5, IL-13) and inflammatory factors (IL-6, IL-17A, IL-10); and inhibit the production of Th1 cytokines (IFN-γ, IL-2). However, the allergic symptoms of mice sensitized by intraperitoneal injection were the most obvious among the three models. The level of serum antibodies in intraperitoneal injection group was significantly higher than control. Subsequently, 16S rRNA sequencing technology was used to analyze the intestinal flora of mice. The results showed that the abundance of Firmicutes in the wheat protein sensitized group was lower than that in the normal group, while the abundance of Bacteroidetes was higher, and Lactobacillus was the difference marker in normal group. Bacterial species diversity analysis showed that the species richness and diversity of intestinal flora in mice were decreased, the difference between mice induced by intraperitoneal injection and normal control group mice was the most significant. Taken together, these results show that among three sensitization methods used to build a mouse model with aluminum hydroxide as adjuvant, intraperitoneal injection is the comparably best way to build a mouse sensitization mode.